A cartografia escolar e as inteligências múltiplas no ensino de geografia: contribuições das geotecnologias no ensino fundamental - Rizzatti, Maurício (2018)
Geography has always been linked to the languages of maps, which act as a system of representation composed of signs that represent physical and human aspects of reality. Like this, student-centered activities allow them to understand where they are located. In the School Cartography it is possible to develop resources linked to the lived space through the application of Theory of Multiples Intelligences (MI), proposed by Howard Gardner. In this context, this work has as main objective to study / identify the contribution of the Multiple Intelligences Theory from the use of geotechnologies in the construction of geographic and cartographic knowledge in Elementary School. The research has a qualitative and quantitative approach, since it discusses subjective elements related to learning, as well as quantifies the data collected to support the discussion. At start, a theory rewiew was made on MI, School Cartography and geotechnologies to base the research. In order to respond to the proposed objectives, the activity was applied to the Santa Helena Municipal School of Elementary Education, located in the Camobi neighborhood, Santa Maria (RS), in the 8th grade, in 2018. In the first contact with the students, a questionnaire was applied to evaluate the previous knowledge in Cartography. Subsequently, a pedagogical workshop was teched in which the concepts of Cartography, mapping techniques and practices were explained to the research subjects, as well as to motivate the MI. Next, a base map of the central region of the Camobi neighborhood (analogic) and another of land use and occupation of the Camobi neighborhood (digital) was created. In addition, a fieldwork was carried was possible to review cartographic concepts approached during the pedagogical workshop, in addition to the motivation of Naturalistic, Visual-Spatial, Logical-Mathematical and Personal Intelligence, mainly. Finally, a questionnaire was applied again, which served to evaluate students' understanding of the topics developed. From the data analysis, it was noticed that the activity presented positive results, being verified an evolution of the variables developed. In addition, the students demonstrate interest in the use of geotechnologies (satellite images, GPS, mapping programs) in Geography classes. Most of the students were able to assimilate concepts pertinent to spatial orientation using cardinal and collateral points, distance estimation, types of visions and the cartographic alphabet after the activity. The exercise of identifying the landscapes in cartographic documents, in the second questionnaire, was performed through the MI (Musical, Spatial, Intrapersonal and Pictorial), presenting an excellent result. it is recommended that teachers know the MI as an innovative learning tool to allow the development of activities that contextualize the lived space of the students, allowing them to understand in a variety of ways a thematic, based on their subjective knowledge. It should be highlight that MI applications contribute to greater efficiency in the teaching-learning process.